Understanding the Determinants of ‘Shared Control’ in Early Childhood Education in Ghana - Nyamekye, Ernest (Papanda Publisher, 2024)
Developing children who are autonomous learners and able to contribute constructively to decision-making, forms part of the reasons why the Ghana Education Service, in the year 2019, introduced the Standards-based curriculum for basic education in Ghana. Teachers were, thus, tasked to adopt the constructivist instructional philosophy to help realize this educational goal. Using a sequential mixed method, this research involved basic schools in the Sunyani-west municipal of Ghana as cases. The current study investigated the practice of shared control as a way of developing children’s autonomous learning abilities. The results of the study indicate that teachers hardly allowed learners to contribute to the management and planning of instruction. Teachers’ perception of the learners’ limited cognitive ability, policy constraints (lesson planning system, examination-driven nature of the curriculum), and some socio-cultural factors significantly contributed to the minimal practice of shared control during instruction. Further results show that the GES, ironically, worked against the possibility of ensuring shared control. Recommendations have, therefore, been offered for the consideration of policymakers and curriculum implementers.